Parents' Opinion on the Effects of Aquatic Physiotherapy on Delayed Motor Development in Infants (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2024)
Background. Aquatic therapy is commonly utilized in the rehabilitation of children with developmental disabilities and as a form of physical activity in water for children without developmental disabilities.The aim. To analyze parents' opinions regarding the impact of physiotherapy in water on the delayed motor development of babies aged 2–9 months.Methods. Ten parents whose babies were diagnosed with motor developmental disorders and received aquatic physical therapy for motor developmental delay were interviewed during the study. A semi-structured interview comprising 18 questions was employed in the qualitative study.Results. The study revealed that parents often notice developmental disorders in their babies when they fail to achieve age-appropriate milestones, leading to later diagnosis by doctors. Following the diagnosis of motor development disorders, doctors recommended various treatment methods to the participants. While parents primarily selected physiotherapy as the main treatment method, they also opted for aquatic physiotherapy as an additional approach for enhanced effectiveness. The Halliwick method was commonly employed to address motor development disorders. Almost all participants expressed willingness to recommend aquatic physiotherapy to friends or acquaintances if their children were diagnosed with motor development disorders.Conclusions. Parents emphasized that water physiotherapy improved their babies' motor skills and had a calming and relaxing effect. Most interviewees indicated a positive inclination towards recommending aquatic physiotherapy, considering it an effective intervention. Keywords: physical therapy in water, motor development, parents, attitudes, babies.